Optimization of Literacy Program as an Effort to Improve Reading Interest of Elementary School Students at Indonesian School Makkah - Nisa, Khoirun; Tharaba, M. Fahim; Nur, Muhammad Amin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Low reading ability in Sekolah Indonesia Makkah shows that educational efforts have not succeeded in increasing students' interest in reading towards knowledge, because currently their interest in reading is very minimal. Through the reading literacy program, it is hoped that students can improve their understanding of basic literacy. The purpose of this study is to determine and analyze the planning, implementation and results of the implementation of the literacy program as an effort to increase the reading interest of elementary school students at Sekolah Indonesia Makkah.This research applies a qualitative and quantitative approach.This type of research applies a qualitative observation study. This research is located at SD Sekolah Indonesia Makkah which is located in Mecca, Saudi Arabia and the subjects of this research are class II B students.Indata collection using techniques, interviews, observations, and documentation. Qualitative data analysis is done interactively and continuously until all data is collected completely. Consists of data condensation, data presentation, and drawing conclusions.Based on the results of research that has been conducted by researchers regarding the title of optimizing literacy programs as an effort to increase reading interest in elementary school students of Sekolah Indonesia Makkah, it can be concluded that the planning, implementation of this literacy program has the results of implementing the literacy program as an effort to increase students' reading interest, namely increasing self-confidence, often practicing reading, practicing pronunciation of words, practicing proper intonation, practicing reading with a clear voice, enriching vocabulary, improving writing skills, and understanding the meaning of reading. And the school library becomes more alive because of the presence of students who take the time to read there so that students are formed who make reading a habit in learning activities.